First results from the 63Cu(α,γ)67Ga reaction study for nuclear astrophysics purposes - Peoviti, Maria; Patronis, Nikolaos; Axiotis, Michail; Foteinou, Varvara; Rogalla, Detlef; Maragkos, Fotios; Harissopulos, Sotirios (HNPS Advances in Nuclear Physics, 2023)
The 63Cu(α,γ)67Ga reaction cross-section was measured in the energy range between 5 and 9 MeV, which is relevant to p-process nucleosynthesis. The experiment was conducted at the Dynamitron Tandem Laboratory, of the Ruhr-University Bochum in Germany, by applying the 4π γ-summing method, using a 12"×12" NaI(Tl) single crystal scintillator. The preliminary results are compared with previous measurements and theoretical TALYS calculations as well.